EFEKTIVITAS PENGENDALIAN PENYAKIT ANTRAKNOSA SECARA ORGANIK TERHADAP PRODUKSI TANAMAN CABAI RAWIT (Capsicum frutescens L.) (Kajian dalam Polibag) - imam habibi (Universitas Islam Kadiri, 2019)
Cayenne pepper (Capsicum frutescens L.) is very prospective and potential in an effort to improve the standard of living farmers. Market demand for chili is quite high, ranging from traditional markets to supermarkets. The problem of productivity of cayenne fruit both in quality and quantity is disrupted due to the attack of antracnose caused by Colletotricum sp. One effort to control antracnose is to control organically. The implementation of this study began in January 2019 until april 2019. This research was conducted in the rice fields of rejomulyo village, Kota subdistrict, kediri city. The altitude of ± 55 mdpl, has an alluvium soil structure, gray-brown alluvial soil type and soil pH 5-6. This study used a non-factorial randomized block design (RBD) which was repeated 4 times and consisted of 7 treatments : A (Inorganic), B (organic ZPT 20 ml/plant), C (micorrhiza 105 cfu/ml), D (manure 40 g/plant), E (organic ZPT 20 ml/plant + micorrhiza 105 cfu/ml) , F (organic ZPT 20 ml/plant + manure 40 g/plant) and G (micorrhiza 105 cfu/ml + 40 g/plant). The results showed that threatment A (inorganic) (281,46 g) was efective for increasing the quatity of cayenne (Capsicum frutescens L.) in addition, treatment D (mature 40 g/plant) (82%), E (organic ZPT 20 ml/plant + micorrhiza 105 cfu/ml) (82%) and G (micorrhiza 105 cfu/ml + 40 g/plant) (82%) is effective to inhibit the disease intensity (%) of antracnose. However, treatment E (organic ZPT 20 ml/plant + micorrhiza 105 cfu/ml) was most effective in controlling antracnose disease and increasing the production of the number of cayenne fruit (Capsicum frutescens L.) Keywords : micorrhiza, effectiveness of Colletotricum sp. cayenne pepper, manure, Organic ZPT